Solution Diversity in Planning - Coman, Alexandra (Proceedings of the AAAI Conference on Artificial Intelligence, 2021)
Diverse planning consists of generating multiple different solutions for the same planning problem. I explore solution diversity, based on quantitative (domain-independent) and qualitative (domain-dependent) distance metrics, in deterministic and nondeterministic planning domains.